Respuesta :

Answer:

  D. [tex]f^{-1}(x)=\log_2{(x-6)}[/tex]

Step-by-step explanation:

Solve x = f(y) for y:

  x = 2^y +6

  x -6 = 2^y . . . . subtract 6

  log2(x -6) = y . . . . take the log base 2 . . . . matches choice D

Answer:

The answer is D

Step-by-step explanation:

In order to find out the inverse of the function, you have to express a new function where the independent variable must be "y" instead of "x".

So, you have to reorganize the base function and then free the variable "x".

[tex]f(x)=2^x+6\\f(x)=y\\y=2^x+6\\2^x=y-6\\log_2(2^x)=log_2(y-6)\\x*log_2(2)=log_2(y-6)\\log_2(2)=1\\x=log_2(y-6)\\[/tex]

Then, we recall "y" as "x" and [tex]x=f^-^1(x)[/tex]

Finally, the answer is:

[tex]f^-^1(x)=log_2(x-6)[/tex]